A reflection on the impact of the practice of indicators on the school performance: Academy of Guelmim Oued Noun - ACHIBANE , Mustapha; MAZZINE , Mohammed; ELHALOUI , Adil (Revue Internationale du Chercheur, 2021)
Over the past two decades, the use of management tools has revolutionized the management and the governance of the educational systems. These management tools are the result of a new market managerial logic (known as the new public management NPM) infused into the public sphere and made the State one enterprise among others, subject to the principles of rationality and the requirement of effectiveness and efficiency of their actions (performance of public action). In the name of the performance, the new public management recommended the instrumentation of the State through the intensive introduction of management tools as practiced in the private sector, the indicators. This article proposes an evaluation of the effect of the indicators on the performance of schools in Morocco, a country that has initiated public reforms for a few years in a new performance approach inspired by the NPM movement. The objective is to examine the impact of the practice of indicators on school performance.